Banished Bodies and Spectral Identities: The Aging Actress in William Hazlitt’s Retirement Essays - Martinović, Nevena (Lumen, 2020)
This article argues that eighteenth-century theatrical reviews and biographical descriptions equate the physical decline of the aging actress with the loss of her identity. It analyses disappearing selfhood through an investigation of the intersection of gender and age in William Hazlitt’s essays on retiring players: namely, “Miss O’Neill’s Retirement,” “Mr. Kemble’s Retirement,” and “Mrs. Siddons’ Lady Macbeth.” In these essays, Hazlitt suggests that the actress only maintains her public identity through an early departure from the stage. This is enforced by societal understandings of normative and desirable femininity as youthful. To emphasize the feminine loss that accompanied aging, Hazlitt and his contemporaries would often juxtapose a player’s physical body with those of younger players, as well as with the memory—or ghost—of its own younger form.